Vietnamese learners’ attitudes towards world Englishes - Tam, Nguyen Thi Dan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
English has become the lingua franca facilitating communication among countries around the globe. Globally, a huge range of industries including mass media, medicine, travel, business, biology and so forth have all been relying on the English language for international cooperation and business. Therefore, many studies have stated that non-native speakers of English outnumber native speakers of English. Because most global communication happens among non-native speakers of English, there is a crucial need to acknowledge varieties of English around the world, or World Englishes instead of English only. However, despite numerous studies which call for the recognition of World Englishes, the roles of World Englishes are still underestimated. In Asia, especially in Vietnam, the ideology of ’native accent’ is dominant, so the importance of World Englishes is totally ignored. In order to raise a concern of this issue for teachers, educators and educational policy officers as well as to prepare students for successful learning English in the future, this paper is going to report a case study that explores the status of World Englishes in Ho Chi Minh City, particularly among TESOL adult students. The findings reveal participants’ attitudes towards native and non-native accents of English, their rationales of the attitudes as well as their frequency of English speakers. This paper suggests an innovative solution for English language planning, teaching, and learning when using English as an international language in this modern world.